'Building back better' along the Sanriku coast of Tohoku, Japan: five years after the '3/11' disaster. Issue 6 (November 2017) - Edgington, David W.
Abstract : This paper addresses the concept of 'build back better' and its application to reconstruction along the Sanriku coastal region, which was affected by a devastating tsunami following the Great East Japan Earthquake of March 2011. I argue that although the Japanese government applied build-back-better approaches ( fukkõ in Japanese), there have been contradictions, challenges and contestations that have delayed the successful recovery of the affected communities. Empirical material collected from field trips to north-east coastal Japan revealed many problems that have impeded this recovery in the first five years of the rebuilding programme. The results question the usefulness of the build-back-better approach to reconstruction.